REPRESENTASI SOSIAL PEREMPUAN “CANTIK” DALAM IKLAN POND`S KOSMETIKS - Siti Khadijah (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2013)
This paper discusses the social representation of women "beautiful" in advertisements Pond `s cosmetics. beautiful definition keeps changing from time to time, one of only guest formation is the result of mass mediated adver-tising there. Construction of the concept of beauty in advertising on television `s Pond can be seen in the form of visual and copy that into representation and conception of female beauty. Brand ambassadors who represent the beauty products is a sign to represent the concept of beauty presented by Pond `s. Al-most the entire ad `s Pond starring celebrities who raised the themes of the sheer physical beauty like smooth white skin, slim, free acne, dark spots free and without wrinkles on the face